Seroprevalence, Associated Factors, and Fetomaternal Outcome in Pregnant Women That Tested Positive to Hepatitis E Antibodies in Nigeria - Valentine Chimezie Okwara; Ikechukwu Innocent Mbachu; Victor Ikechukwu Ndububa; Henry Chima Okpara; Chioma Pauline Mbachu (Obstetrics and Gynecology International)
Background. Hepatitis E virus infection is an emerging disease with varied courses in pregnancy. There is a dearth of statistics among pregnant women. Aim. To evaluate the prevalence, associated factors, and pregnancy outcome in women that tested positive for hepatitis E virus (HEV) antibodies in pregnancy. Research Methods. This was a cross-sectional study conducted among pregnant women at a teaching hospital in Nigeria. Relevant information was collected using a structured questionnaire. Blood was collected from each of the participants, and the serum was used to determine the presence of hepatitis E immunoglobulin M (IgM) and G (IgG). The data were analysed using SPSS version 23. Associations between variables were determined at a p value of <0.05. Results. A total of 200 pregnant women participated in this study. The prevalence of HEV infection among pregnant women was 28.00% (56/200). The mean age was 30.11 ± 5.88. Hepatitis E infection was significantly associated with age (p value = 0.028), method of faecal disposal (p value = 0.043), and source of drinking water (p value = 0.039). A total of 9/200 (4.50%) stillbirths were recorded with 3/9 (33.33%) in women that tested positive for HEV antibodies. About 4/200(2.00%) miscarriages were recorded, and 2/4 (50.00%) were in women that tested positive for HEV antibodies. Hepatitis E infection was not significantly associated with perinatal outcome (p value = 0.45). Only 1/56 (0.50%) maternal death was recorded among women that tested positive to hepatitis E, and none was recorded among those that tested negative to hepatitis E antibodies. Conclusion. There was a significant statistical association between HEV infection and age, method of faecal disposal, and source of drinking water. This underscores the importance of the provision of clean water and safe faecal disposal. Hepatitis E virus infection did not significantly affect the foetal and maternal outcomes.